Have Middle-Class Earnings Risen in Canada? A Statistical Inference Approach - Charles Beach (Queen's University, Department of Economics, 2017)
This paper extends the statistical inference approach developed in Beach (2016) to look at income changes over different regions of an income distribution. Specifically, it looks at relative-mean earnings (RME) ratios and mean earnings levels for lower earners, middle-class (MC) workers and higher earners in Canada since 1970. Formulas are developed for (asymptotic) standard errors of these distributional statistics. The most consistent pattern since 1980 has been the marked decline in RME for MC workers, which has been highly statistically significant. Since 2005, however, real earnings levels have increased significantly and have been broadly shared across these earnings groups.
Keywords: C12; C46; J20; J31; 330; Income equality; Canadian earnings; Statistical inference